THE RELATIONSHIP BETWEEN ETHNOCULTURAL EMPATHY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AMONG PUBLIC SERVANTS IN SABAH - Razima Hanim Osman; Mariny Abdul Ghani; Norzaliza Alis, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Organizational citizenship behavior (OCB) throughout literature provides evidence that benefits both employees and the organizations in terms of increasing the level of employees' well-being, work satisfaction, customers' satisfaction as well as the quality of work performance. Hence, it is important to understand the possible reasons behind the occurrence of OCB to increase the likelihood of employees engaging in OCB. Based on the prosocial motivational concept, empathy is the main motivator to helping behaviors thus open up the possibility of linkage between empathy and extra-role behaviors such as OCB. Moreover, this linkage is important for public employees especially those who are working in organizations that have multi-ethnic employees as well as providing services to meet vast societal needs and demands. The present article set out to examine the relationship between ethnocultural empathy and OCB among public employees in Sabah. A cross-sectional survey was used to gather a response of 213 public employees who are working in the Jabatan Pendaftaran Negara Negeri Sabah (JPN) based on the selected districts in Sabah. Results showed positive relationships between organizational citizenship behavior-individual (OCBI) with empathic awareness (EA) dimensions. Results also showed positive relationships between organizational citizenship behavior-organization (OCBO) with empathic feeling and emotion (EFE). By focusing on the aspect of culture in empathy such as ethnocultural empathy can help researchers to understand how culture influences the cognition and emotions of individuals to understand other people's experiences especially those who have a different cultural and ethnic background. Apart from that, the concept itself strengthens the ability to understand the thinking and feeling of others in their cultural context thus increases the likelihood to perform extra-role behavior such as OCB.